Solução das equações de Navier-Stokes e da equação de transporte por um método de elementos finitos estabilizado pela técnica de separação baseada na característica - Baggio, Gustavo Aparecido Pita [UNESP] (2015)
The classical finite element method called the method of Bubnov-Galerkin or Galerkin Method (GFEM) is optimum for solving diffusion problems, however, in case of problems with dominant convection as in many problems of fluid flow, the GFEM produces oscillating solutions for high Reynolds numbers. Several techniques have been associated with the discretization of the convective terms in the Navier-Stokes equations to remedy the deficiency of GFEM. One of such techniques is denominated in literature as Characteristic Based Split (CBS) and has been applied successfully to stabilize the solutions of convective problems using GFEM. In this work, the GFEM associated with the Characteristic Based Split (CBS) scheme will be applied to simulate two and three-dimensional incompressible fluid flows